Vegetation and climate zones based carbon use efficiency variation and the main determinants analysis in China. (April 2020) - Chuai, Xiaowei; Guo, Xiaomin; Zhang, Mei; Yuan, Ye; Li, Jiasheng; Zhao, Rongqin; Yang, Wenjuan; Li, Jianbao
Highlights: Cold and dry environments always contain vegetation with high NPP/GPP ratios. Warm and wet environments always contain vegetation with low NPP/GPP ratios. NPP/GPP ratio weakly increased over the past 16 years. Both moderate precipitation and temperature can increase the NPP/GPP ratio. Abstract: NPP/GPP ratio is related to the allocation of photosynthesized products by plants. The examination of this ratio and its exterior controlling factors are very critical for understanding the carbon cycle. China covers a large area and contains diverse ecosystems and climate conditions, while, extensive studies of the NPP/GPP ratio and its exterior controls have not yet been conducted. This study examines the 16-year (2000–2015) mean NPP/GPP ratio distribution in space, its spatiotemporal changes, its response to exterior controls in each ecosystem, and how ongoing climate changes affect the NPP/GPP ratio over time. This study found, cold and dry environments usually contain vegetation with high NPP/GPP ratios, while the opposite is true for warm and wet environments. However, the highest NPP/GPP values do not always occur in the coldest and driest environments, and the lowest values do not always occur in the warmest and wettest environments. The NPP/GPP ratio weakly increased over the past 16 years. Generally, both moderate precipitation and temperature can increase NPP/GPP ratio. Temporally, more grids are positively correlated with changes in precipitation and negatively correlated with changes in temperature.